The machinery for Raising Capital by companies through debt finances In Nigeria. (2011)
This study aimed at examining critically the legal machinery for creating debenture by companies, rights of the debentures holders and methods of enforcement of the debenture in Nigeria. The machinery for raising capital through debenture is not well articulated in the Companies and Allied Matters Act (CAMA) 1990. The position of the law on the rights and duties of the parties to a floating charge is inadequate and reforms are urgently required as current edition of the law allows for fraud on unwary parties. This study’s submission was that the law be reviewed in such a way that many loopholes like the ninety day rule in Nigeria is changed, either reduced or changed to one of immediate notification of such transaction to the commission, to ensure some level of certainty in this area of the law.